Development of Strategy for Culture-Based Tourism Village in Tempilang Village, Bangka Barat, Indonesia - Rulyanti Susi Wardhani; Devi Ayuni; Minrohayati Minrohayati (Jurnal Internasional Ilmu Pengetahuan Terapan bidang Pariwisata dan Events, 2021)
Tempilang Village is one of the culture-based villages in Bangka Barat District which has historical value and various cultural attractions. However, there are some factors which may inhibit the position of Tempilang Village as a tourism-based village, such as the inadequate role of the local district government in managing cultural assets, especially in its utilization as a tourism attraction, community involvement in promoting villages and the role of cross sectors in development of cultural and economic potentials in Tempilang Village. This research aimed at formulating a sustainable cultural tourism development strategy to enhance the cultural potential and economic condition of the surrounding local community. This research used descriptive qualitative analysis, content analysis, IFAS EFAS and SWOT matrix. The results of the IFAS and EFAS analysis in the SWOT Cartesian diagram indicated that Tempilang Village is in a favorable position with the dominant strength and opportunity factors and growth strategy as the main focus of the development strategy. Based on the results of analysis of internal and external factors using the SWOT matrix, there were four main strategies for sustainable tourism development to be implemented in Tempilang Village, including strategies for optimizing the management of cultural tourism, strategies for optimizing the potential of home based enterprises in the village to support tourism activities, utilizing intangible culture in the village as a product of cultural tourism and managing tangible cultural assets in the village through opportunities for cooperation.